Experimental Determination of Photo Luminesscense Quantum Yield of CdSe Quantum Dots - Binh, Nguyen Thanh (Communications in Physics, 2016)
The fluorescence quantum yield or the efficiency of the fluorescence process is defined as the ratio of the number of photons emitted to the number of photons absorbed. In this report the experimental method to determinate photo luminescence (PL) quantum yield (QY) of CdSe quantum dot will be described. The experimental condition which depends on QY will be investigated. The QY values of CdSe which were prepared at Nano Materials Physics Laboratory Research Center for Dielectric and Advanced Matters Physics Pusan National University will be carried out and compared with the commercial CdSe sample.